2021
DOI: 10.1093/function/zqab001
|View full text |Cite
|
Sign up to set email alerts
|

Heat Treatment Improves Hepatic Mitochondrial Respiratory Efficiency via Mitochondrial Remodeling

Abstract: Non-acholic fatty liver disease, or hepatic steatosis, is the most common liver disorder affecting the western world and currently has no pharmacologic cure. Thus, many investigations have focused on alternative strategies to treat or prevent hepatic steatosis. Our laboratory has shown that chronic heat treatment (HT) mitigates glucose intolerance, insulin resistance, and hepatic steatosis in rodent models of obesity. Here, we investigate the direct bioenergetic mechanism(s) surrounding the metabolic effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 63 publications
2
10
0
Order By: Relevance
“…Supporting the role of HSP72 in mediating these effects, we have also shown that increased insulin-stimulated glucose uptake in response to heat treatment only occurs in the presence of normal HSP72 levels in siRNAtreated glycolytic muscles of rats bred for low-capacity running (36). We came to the same conclusion in a liver-specific HSP72 KO mouse model, demonstrating that the normal improvements in glucose control with heat treatment are eliminated in the absence of hepatic HSP72 (37).…”
Section: Improved Glucose Control Can Enhance Mitochondrial Functionsupporting
confidence: 66%
See 2 more Smart Citations
“…Supporting the role of HSP72 in mediating these effects, we have also shown that increased insulin-stimulated glucose uptake in response to heat treatment only occurs in the presence of normal HSP72 levels in siRNAtreated glycolytic muscles of rats bred for low-capacity running (36). We came to the same conclusion in a liver-specific HSP72 KO mouse model, demonstrating that the normal improvements in glucose control with heat treatment are eliminated in the absence of hepatic HSP72 (37).…”
Section: Improved Glucose Control Can Enhance Mitochondrial Functionsupporting
confidence: 66%
“…3I). Repeated bouts of heat therapy (nine sessions at 42°C every 72 h for 4 wk) improve mitochondrial respiration, reduce mitochondrial H 2 O 2 emission, and increase proteins involved in mitochondrial transport, mitochondrial organization, and protein folding (37) (representative data in Figs. 3E-H).…”
Section: Mitophagy Enhances Mitochondrial Quality Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…In the latest issue of Function , Von Schulze et al 1 elegantly combine metabolic physiology with sophisticated bioenergetic analyses to elucidate the acute and chronic impacts of heat treatment (HT) across the hepatic mitochondrial network. This work is based on a collection of evidence, from this group and others, suggesting that impairments in mitochondrial functionality and/or quality control may underly non-alcoholic fatty liver disease (NAFLD).…”
Section: A Perspective On “Heat Treatment Improves Hepatic Mitochondr...mentioning
confidence: 99%
“…From a therapeutic perspective, the results of Von Schulze et al 1 have far-reaching implications, particularly with respect to individuals suffering from NAFLD for which exercise interventions are contraindicated. With respect to hepatic mitochondrial biology, one of the most interesting findings of this work centers upon the observation that chronic HT both improved intrinsic bioenergetic efficiency while simultaneously decreasing hepatic mitochondrial content.…”
Section: A Perspective On “Heat Treatment Improves Hepatic Mitochondr...mentioning
confidence: 99%